Culture and agency theory: the case of Malaysia - Mustapha, Mazlina (Medwell Journals, 2017)
This study examines the effect of culture (ethnicity) on agency costs in relation to agency theory in Malaysian business environment. It explores the monitoring costs of the businesses controlled by different ethnic groups in Malaysia. These businesses are those controlled by Chinese and Malays which are claimed to be the main groups, dominate much of the socio-economic in Malaysia. In addition, the increased in foreign investments in Malaysia which have different culture impact in the organizations is also examined. The result indicates that there is a significant relationship between the monitoring costs demanded by businesses controlled by different ethnic groups in Malaysia. Chinese controlled businesses appear to have significant negative relationship with monitoring costs while malay controlled businesses show a significant positive relationship with monitoring costs.